Optimisation of shock absorber process parameters using failure mode and effect analysis and genetic algorithm - Arokiasamy Mariajayaprakash; Thiyagarajan Senthilvelan; Krishnapillai Vivekananthan (Journal of Industrial Engineering International, 2013)
The various process parameters affecting the quality characteristics of the shock absorber during the process were identified using the Ishikawa diagram and by failure mode and effect analysis. The identified process parameters are welding process parameters (squeeze, heat control, wheel speed, and air pressure), damper sealing process parameters (load, hydraulic pressure, air pressure, and fixture height), washing process parameters (total alkalinity, temperature, pH value of rinsing water, and timing), and painting process parameters (flowability, coating thickness, pointage, and temperature). In this paper, the process parameters, namely, painting and washing process parameters, are optimized by Taguchi method. Though the defects are reasonably minimized by Taguchi method, in order to achieve zero defects during the processes, genetic algorithm technique is applied on the optimized parameters obtained by Taguchi method.
Keywords: 650; Ishikawa diagram; FMEA; Taguchi method; Genetic algorithm